The Relationship Between Social Support and Palliative Patient Compliance in Undergoing Home Care - Puspitarini, Nurul Aisyiyah; Mulat, Trimaya Cahya (International Journal of Health Sciences, 2025)
Background: Palliative care patients require comprehensive support from their families, healthcare professionals, and social environment to effectively undergo treatment. Patient compliance with home care is greatly influenced by adequate social support. Objective: To determine the relationship between social support and compliance of palliative patients in undergoing home care. Methods: This study used a cross-sectional design with a sample size of 60 palliative care patients undergoing home care. The research instruments used a social support questionnaire and a care adherence questionnaire. Data analysis was performed using the chi-square test with a significance level of p < 0.05. Results: The study showed a significant relationship between social support and palliative care patient compliance with home care (p = 0.002). Patients with high social support were more compliant with care compared to patients with low social support. Conclusion: Social support plays a crucial role in improving compliance in palliative care patients undergoing home care. Care interventions should involve family and the surrounding community in providing social support to patients.